2017
DOI: 10.1016/s1875-5364(17)30042-0
|View full text |Cite
|
Sign up to set email alerts
|

Saposhnikoviae divaricata : a phytochemical, pharmacological, and pharmacokinetic review

Abstract: Saposhnikoviae divaricata (Turcz.) Schischk (SD) is a traditional Chinese herb commonly used to treat clinical conditions such as rheumatism and allergic rhinitis. This review article evaluates a collection of works on in vitro and biochemical studies of SD. The discourse on the diverse class of chromones and coumarins in SD offers an insight to the pharmacological effects of these bioactive constituents as anti-inflammatory, analgesic, immunoregulatory, antioxidative, and anti-proliferative agents. It is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…Phytochemical studies have revealed that there are approximately 100 compounds with different structural patterns isolated from S. divaricata, including chromones, coumarins, acid esters, polyacetylenes, volatile oils, polysaccharides, and inorganic elements (1,4,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) as shown in Appendixes 3-9.…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochemical studies have revealed that there are approximately 100 compounds with different structural patterns isolated from S. divaricata, including chromones, coumarins, acid esters, polyacetylenes, volatile oils, polysaccharides, and inorganic elements (1,4,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) as shown in Appendixes 3-9.…”
Section: Phytochemistrymentioning
confidence: 99%
“…They have extremely diverse structures, which are divided into simple coumarins, pyranocoumarins, furanocoumarins, and other coumarins. (1,21,22) At present, a total of 35 coumarins, primarily furanocoumarins and pyranocoumarins, have been identified from S. divaricata (Appendixes 4 and 5). Among them, the 17 furanocoumarins isolated include bergapten (18), byakangelicin (19), deltoin (20), imperatorin (21), isoimperatorin (22), isobergapten (23), marmesin (24), methoxy-8-(3-hydroxymethylbut-2-enyloxy)-psoralen (25), nodakenetin (26), oxypeucedanin hydrate (27), phellopterin (28), psoralen (29), sapodivarin (30), xanthotoxin (31), 5-hydroxy-8-methoxypsoralen (32), nodakenin (33), and xanthoarnol (34).…”
Section: Chromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…e HCA was applied to analyze the concentrations of GC, G, GV, V, GH, and H. e result indicated that 54 batches of commercial SRs (the 51st batch of SR was self-contained, not considered) were divided into two categories as shown in Figure 5. On the one hand, Cluster 1 consisted of 45 batch samples (34,55,14,54,1,11,4,15,36,39,10,40,41,42,35,18,47,7,28,43,46,23,27,50,16,29,2,3,5,21,9,12,8,38,19,44,13,37,24,48,26,20,32,33,30), in which their total content of six components was not more than 8 mg•g −1 . On the other hand, the remaining 9 batch samples (6,31,25,22,45,…”
Section: Hcamentioning
confidence: 99%
“…SR has several components: chromones, polysaccharides, coumarins, volatile oils, and other components [9][10][11][12]. It is worth mentioning that chromones are the most representative components in SR. On the one hand, there are extremely abundant content [13].…”
Section: Introductionmentioning
confidence: 99%